Seropositividad de toxoplasmosis en pacientes VIH empleando unidades arbitrarias de anticuerpos - Guerra Manihuari, Christian Andy (2024)
Toxoplasma gondii is the parasite that causes Toxoplasmosis, an infection that usually affects patients with HIV infection, which creates a diagnostic challenge. The aim of this study was to determine the seropositivity of HIV-infected patients by using arbitrary antibody units against Toxoplasma gondii. A total of 100 serum samples were collected from HIV-positive patients from the different provinces of the Loreto region. IgG antibody titers were measured using an Enzyme Linked Immunosorbent Assay (ELISA). Subsequently, two mathematical approaches (traditional method, and antibody arbitrary unit methods) were used to define a cut-off point based solely on the data analyzed, in order to determine the seropositivity of our population (seronegative, seropositive). It was observed that seropositivity for the first mathematical approach resulted in 89% seropositive and 11% seronegative; while the second approach resulted in 95% seropositive, 3% seronegative, and 2% indeterminate. In conclusion, both approaches were shown to determine the seropositivity of a population. However, the use of arbitrary antibody units allows us to generally express results (seropositive and seronegative) without the need to have a population not exposed to infection.